The wealth decumulation behavior of the retired elderly in Italy: The importance of bequest motives and precautionary saving - Luigi Ventura; Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2020)
In this paper, we analyze the wealth accumulation and saving behavior of the retired elderly in Italy using micro data from the "Survey of Italian Households' Income and Wealth," a panel survey of households conducted every two years by the Bank of Italy. We find that, on average, the retired elderly in Italy are decumulating their wealth (dissaving) but that their wealth decumulation rates are much slower than expected. Moreover, we also find that more than 40 percent of the retired elderly in Italy are continuing to accumulate wealth and that more than 80 percent are doing positive amounts of saving. Thus, the Wealth Decumulation Puzzle (the tendency of the retired elderly to decumulate their wealth more slowly than expected) appears to apply in the case of Italy, as it does in most other countries, before as well as after the Global Financial Crisis. Moreover, our regression analysis of the determinants of the wealth accumulation and saving behavior of the retired elderly in Italy suggests that the lower than expected wealth decumulation rates and dissaving of the retired elderly in Italy is due largely to intergenerational transfers (bequests and inter vivos transfers) and saving for precautionary purposes, especially the former.
Keywords: D12; D14; D15; D64; E21; J14; 330; Aged; bequests; bequest intentions; bequest motive; dissaving; elderly; estates; household saving; Italy; inheritances; inter vivos transfers; intergenerational transfers; life-cycle hypothesis; life-cycle model; life-cycle theory; precautionary saving; retiredelderly; saving; wealth; wealth accumulation; wealth decumulation; wealth decumulationpuzzle